2018
DOI: 10.1021/acs.jnatprod.8b00450
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrochalcone Glucosides from the Subaerial Parts of Thonningia sanguinea and Their in Vitro PTP1B Inhibitory Activities

Abstract: Six new and four known dihydrochalcone glucoside derivatives (1-10), the phenylpropanoid coniferin (11), and the lignans (+)-pinoresinol (12) and lariciresinol (13) were isolated from the subaerial plant parts of Thonningia sanguinea in the course of a screening campaign for new antidiabetic lead compounds. The structures of the new substances were elucidated by HRESIMS, NMR, GC-MS, and ECD data evaluation. 2'- O-(3-Galloyl-4,6- O- S-hexahydroxydiphenoyl-β-d-glucopyranosyl)-3-hydroxyphloretin (4), 2'- O-(4,6- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…830 bar) with the optimized conditions, which limited the flow rate of the used instrument to 0.4 mL/min. Nevertheless, the analysis time was still reduced (factor 1.8, based on the retention time of thA) compared to conventional HPLC [13] and came with a huge gain in resolution. The compounds in the samples were assigned by comparison of retention times and online LC-UV spectra.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…830 bar) with the optimized conditions, which limited the flow rate of the used instrument to 0.4 mL/min. Nevertheless, the analysis time was still reduced (factor 1.8, based on the retention time of thA) compared to conventional HPLC [13] and came with a huge gain in resolution. The compounds in the samples were assigned by comparison of retention times and online LC-UV spectra.…”
Section: Resultsmentioning
confidence: 99%
“…All three were found to be inhibitors of protein tyrosine phosphatase-1B (PTP1B), a negative regulator in insulin pathway signalling, in an in vitro enzyme assay, whereas the three remaining major compounds, namely, 3-hydroxyphloridzin (1), 2′-O-(6-Ogalloyl-β-D-glucopyranosyl)-3-hydroxyphloretin (2), and 2′-O-(4,6-O-S a -hexahydroxydiphenoyl-β-D-glucopyranosyl)-3-hydroxyphloretin (3), showed no activity. ThA was additionally able to increase the level of phosphorylated insulin receptors in a cell-based assay [13]. Furthermore, thA showed cytotoxic activity on a HepG-2 human hepatocellular carcinoma cell line [14].…”
Section: Development and Validation Of A Uhplc-dad Methods For The Quamentioning
confidence: 95%
See 2 more Smart Citations
“…During an ethnopharmacological survey in the province of Uíge in northern Angola, its various traditional uses have emerged, for example, the use against erectile dysfunction, cough, urinal infections, and as an anthelmintic [4]. In a recent study on this plant, we reported the in vitro pharmacological potential of T. sanguinea and some of its secondary metabolites as inhibitors of protein tyrosine phosphatase 1B (PTP1B) [5], a cellular receptor representing a potential target for the treatment of diabetes, obesity, and some types of cancer [6]. The crude methanol (MeOH) extract of the plant batch investigated in the present study contained six dihydrochalcone glucosides as major compounds, which were identified as thonningianin A (thA), thonningianin B (thB), 3- (4) [5,7].…”
Section: Introductionmentioning
confidence: 99%